The Implementation of the Return of Criminal Evidence in the Probolinggo District Court Based on Prosecutor's Regulation Number 7 of 2020 - Hadiah, Hadiah; Dluha, Muhamad; El HF, Kholidazia (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study discusses the implementation of the return of evidence in criminal cases at the Probolinggo City District Attorney's Office based on Prosecutor's Regulation Number 7 of 2020 concerning Asset Recovery. The main focus of this study is to describe the administrative mechanisms and obstacles faced in the process of returning evidence after a court decision with permanent legal force. This research was analyzed using the Lawrence M. Friedman Legal System Theory approach which includes three main elements, namely legal structure, legal substance, and legal culture. The method used is an empirical juridical approach with a combination of legislative and socio-legal approaches. Data was obtained through literature studies, observations, and interviews with prosecutors, evidence officers, and the recipient of goods. The results of the study show that the return of evidence is carried out through the digital service system